2022
DOI: 10.1007/s00464-021-08979-w
|View full text |Cite
|
Sign up to set email alerts
|

The first survey addressing patients with BMI over 50: a survey of 789 bariatric surgeons

Abstract: Background Bariatric surgery in patients with BMI over 50 kg/m2 is a challenging task. The aim of this study was to address main issues regarding perioperative management of these patients by using a worldwide survey. Methods An online 48-item questionnaire-based survey on perioperative management of patients with a BMI superior to 50 kg/m2 was ideated by 15 bariatric surgeons from 9 different countries. The questionnaire was emailed to all members of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Such data are probably due to the minor impact of the patient’s complexity on the robotic approach when compared to laparoscopy. Indeed, robotic procedures allow to overcome SO and SSO patients-related surgical difficulties, due to the aforementioned advantages of robotic technology [ 28 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such data are probably due to the minor impact of the patient’s complexity on the robotic approach when compared to laparoscopy. Indeed, robotic procedures allow to overcome SO and SSO patients-related surgical difficulties, due to the aforementioned advantages of robotic technology [ 28 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 789 MBS surgeons worldwide regarding selection of surgery and management of patients with class IV obesity found that identifying the safest effective procedure for high-BMI patients was a primary challenge. 25 With respect to OAGB, a recent systematic review by Parmar et al that directly compared OAGB to SG and RYGB in class IV and V obesity concluded that the safety of OAGB was equivalent to that of the other two procedures. 16 Still, the existing evidence conflicts on the topic of perioperative complications in higher-BMI patients after OAGB, SG, and RYGB.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 789 MBS surgeons worldwide regarding selection of surgery and management of patients with class IV obesity found that identifying the safest effective procedure for high‐BMI patients was a primary challenge 25 . With respect to OAGB, a recent systematic review by Parmar et al.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 789 MBS surgeons worldwide regarding selection of surgery and management of patients with class IV obesity found that identifying the safest effective procedure for high-BMI patients was a primary challenge [24]. With respect to OAGB, a recent systematic review by Parmar et al that directly compared OAGB to SG and RYGB in class IV and V obesity concluded that the safety of OAGB was equivalent to that of the other two procedures [15].…”
Section: Discussionmentioning
confidence: 99%